City Ordinance No. 45, RENO EVENING GAZETTE, Sept. 6, 1905, at 6, § 7 (Reno, Nevada). - (:unkn) unknown (General Publisher, 1905)
It shall be unlawful for any person within the limits of the city of Reno, to wear, carry, or have concealed upon his person any dirk knife, pistol, sword in case, slung shot, brass knuckles, razor or other dangerous weapon without first obtaining permission from the City Council
--
Keywords: CARRY - CONCEALED